2018
DOI: 10.3389/fpls.2018.00127
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Herbivory in Structuring Tropical Seagrass Ecosystem Service Delivery

Abstract: Seagrass meadows support key ecosystem services, via provision of food directly for herbivores, and indirectly to their predators. The importance of herbivores in seagrass meadows has been well-documented, but the links between food webs and ecosystem services in seagrass meadows have not previously been made explicit. Herbivores interact with ecosystem services – including carbon sequestration, cultural values, and coastal protection. Interactions can be positive or negative and depend on a range of factors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 95 publications
(129 reference statements)
0
45
0
2
Order By: Relevance
“…This increased bite size may also result in the incidental removal of non‐target species, such as unpalatable macroalgae, that smaller fishes avoid, as the feeding morphology of large herbivores can physically constrain their ability to selectively target individual resources (Pollard and Cooke , Scott et al. ). In fact, many parrotfish species appear to be microphages that target cyanobacteria and other autotrophic microorganisms living on or within the algae and substrate they consume, suggesting the majority of macroalgae consumption by parrotfishes may be incidental (Clements et al.…”
Section: Discussionmentioning
confidence: 99%
“…This increased bite size may also result in the incidental removal of non‐target species, such as unpalatable macroalgae, that smaller fishes avoid, as the feeding morphology of large herbivores can physically constrain their ability to selectively target individual resources (Pollard and Cooke , Scott et al. ). In fact, many parrotfish species appear to be microphages that target cyanobacteria and other autotrophic microorganisms living on or within the algae and substrate they consume, suggesting the majority of macroalgae consumption by parrotfishes may be incidental (Clements et al.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline size spectra can be used to assess the health and value of different types of meadows, providing a tool for management to understand how different meadows might provide for ecosystem services such as fisheries (Scott et al. ). Size spectra may also be indicative of the dynamic stability of food webs (Law et al.…”
Section: Discussionmentioning
confidence: 99%
“…Seagrass loss means a loss of a wide range of important ecosystem services, including food web support for endangered fauna (Scott et al. , Sievers et al. ), and a greater understanding of how seagrasses provide these services is required to manage impacts on seagrass (Unsworth et al.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, seagrass can be directly grazed upon. Seagrass herbivory by macrograzers (i.e., fish) and megagrazers (i.e., turtles and dugongs) are important to maintaining ecosystem function and reproduction in balanced ecosystems (i.e., systems with predators, grazers, and seagrasses) (Tol et al, 2017;Scott et al, 2018). With the loss of predators and conservation of large herbivores without habitat consideration, it is suggested that seagrass ecosystem functions could be lost from uncontrolled rates of grazing (Burkholder et al, 2013;Christianen et al, 2014;Heithaus et al, 2014;Scott et al, 2018).…”
Section: Trophic Facilitationmentioning
confidence: 99%